Impact of Vigilante Service Group on Crime Control for Sustainable Development in Ilorin West Local Government Area of Kwara State, Nigeria (Federal University Gusau Faculty of Education Journal, 2026)
This study assesses the impact of vigilante service group on crime control for sustainable development in Ilorin West Local Government, Kwara State. The Population of the study comprised of all community members and vigilante in Ilorin West Local Government. The sample for this study comprised of 120 respondents selected through a dip-hat sampling technique. Descriptive survey design was employed in the study and a questionnaire titled "Impact of Vigilante Service Group on Crime Control for Sustainable Development Questionnaire (IVESGCCSDQ)" with a reliability of 1.9. Four research questions were raised and answered using mean and standard deviation. The results shows that crime constitutes to social problem in the aspect that crime has led to disruption of business activities and crime has led some to marriage divorce in Ilorin West local government area. The following recommendations were suggested: that government should encourage the vigilante group service by allocating adequate fund to execute their duties couple with the provision of ammunitions to protect the populace of a community. The community members should not obstruct the vigilante group during the course of executing their duties in the community like controlling crime.